Clinical and Haematological Disorders in Cats with Natural and Progressive Infection by Feline Leukemia Virus (FeLV) - Biezus, Giovana; Ferian, Paulo Eduardo; da Silva Pereira, Leonardo Henrique Hasckel; Withoeft, Jéssica Aline; Antunes, Marina Mattei; Nunes Xavier, Maysa Garlet; Volpato, Julieta; de Cristo, Thierry Grima; Fonteque, Joandes Henrique; Casagrande, Renata Assis (Acta Scientiae Veterinariae, 2019)
Background: Feline leukemia virus (FeLV) is an important infectious agent in cats, responsible for great health damages and a large death amount. Among the most common clinical disorders caused by FeLV, severe hematological changes are related at the progressive infection, ordinarily presented as cytopenias. Regarding its oncogenic potential, lymphoma and leukemia are the most observed illness originated by the agent. Therefore, this study has the goal of describing and comparing clinical and hematological disorders in FeLV positive cats from a selected population. Materials, Methods & Results: Data of clinical evaluations of felines from a previously performed cross-sectional epidemiological study were compiled. This study obtained the prevalence of FeLV infected cats in Santa Catarina Plateau. Three groups were established from the original sample of 274 cats; Group 1 (control), FeLV negative and none clinical alterations (n = 80); Group 2, FeLV positive and none clinical changes (n = 9); Group 3, FeLV positive cats with clinical disorders (n = 29). Physical and hematological examination data were obtained from the medical records. The clinical changes at Group 3 were mucosal pallor (65.51% [19/29]), neurological disorders (20.69% [6/29]), lymphoma (20.69% [6/29]), coinfections (10.34% [3/29]) and leukemia (6.9% [2/29]). The most observed hematological disorders of Group 3 were anemia (65.51% [19/29]) and thrombocytopenia (62.7% [18/20]). At the complete blood count, the medium erythrocyte and eosinophil count, hemoglobin concentration and hematocrit were lower for Group 3 than the other two groups. The mean number of platelets count were higher for Group 1 than Group 2 and 3. The mean of the other variables remained between reference numbers. However, a descriptive analysis within the groups demonstrated that lymphopenia was observed in 34.48% (10/29) and neutropenia in 17.24% (5/29) at the Group 3. Discussion: The greater FeLV positive cats with clinical alterations number is a result of a sample obtained from a hospital population. In this scenario, cats are submitted to medical appointment in order to solve their clinical signs, not for purpose of infection screening. The frequency of non-neoplasic disease in FeLV positive cats was higher than neoplastic diseases. The mucosal pallor is the most important clinical change and it is an anemia consequence. A large number of clinical signs related in this study was non-specific. All the clinical changes are associated to FeLV infection, regardless the clinical syndrome observed. Neurological disorders frequency at this study was higher than other articles, being related to neoplastic lymphocytes in central nervous system at the resolved cases. Lymphoma and leukemia were the only neoplasms found in this FeLV study. Non-regenerative anemia was the main FeLV associated hematologic change. This disorder is originated by several mechanisms, such as the virus influence on bone marrow precursors and leukemic infiltration. Thrombocytopenia showed lower frequency than anemia and leukopenia, however, it was the second most common alteration in this study, which was observed in Group 2 and 3. The severe cytopenias related in Group 3 are probably due to the destruction or decrease of the production of these cells by the virus replication process. The clinical and hematological disorders found in this study, reveal the serious presentation and usually irreversible situation of this viral infection, originating important health harm to the affected cats.